Diversi Terhadap Tindak Pidana Penghinaan Yang Dilakukan Oleh Anak - Widyananda, Priskila (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Humiliation is a crime that needs attention. Moreover, the impact of today's technology makes crimes easily known to the wider community. Hate speech is one of the most common crimes we encounter on the internet and some are committed by children. RJ as a 16-year-old child who is suspected of having insulted the President of the Republic of Indonesia, who must go through the juvenile justice process conducted by investigators and public prosecutors. The criminal act of insult is regulated in article 310 of the Criminal Code and for the criminal act of insult committed through social media is regulated in article 27 paragraph 3 of Law Number 11 of 2008 concerning Information and Electronic Transactions. Children in conflict with the law are protected in Law Number 23 of 2002 concerning Child Protection. In the judicial process, all law enforcement officials must pay attention to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System as a basis. RJ, as a child in conflict with the law, insulted the President of the Republic of Indonesia by uploading hate speech on his Instagram account. He has gone through a judicial process in accordance with the provisions of Law Number 11 of 2012, where diversion is the method taken to resolve the case, but a diversion agreement was reached. without presenting the victim as a requirement in carrying out diversion as determined according to article 9 paragraph 2 of Law Number 11 of 2012.